Insight Industry 4.0: An Answer to Smart Village Policy Transformation in Indonesia - Annshori, Muhammad Faqih; Bela, Hafizoh Yuelsa; Mikyal Marshalita, Mikyal (Indo-MathEdu Intellectuals Journal, 2024)
This article highlights the perspective of smart village policy development in Indonesia along the entry of technological changes adopted as a form of transformation. The change towards the use of the Internet of Things is marked by the entry of the industrial revolution era 4.0. The village becomes the smallest unit of governance that is expected to adapt quickly and have a positive effect on the community. However, the problem is severe due to the increase in the flow of urbanization of rural communities. Therefore, it is expected that regulations will be present and facilitate basic needs in the village. The final rate of development and growth of smart villages was able to reach 12% per year 2016, exceeding the national economic growth which was only 5% per year at that time. This article is a type of qualitative research by collecting data electronically, including searching extensive literature research and conducting an online survey of smart village policies developing in Indonesia today and in the future. This survey was distributed to rural communities that are included in the priority of smart village development by the Ministry. The number of smart village policy developments covered in this review article, program or policy action, is to achieve the target of 3,000 smart villages with a period of 2020 - 2024. Based on this, key policy findings and recommendations for future smart village programs are presented. The program that has been carried out is the result of previous studies on this topic, so it will be interesting and can be used as recommendations in the future for the government as a policy maker at the national and local levels.